Diagnosis, Prevention and Treatment of Chronic Catarrhal Gingivitis in Children - Ganiev J. I; Xabibova N. N. (Researchparks Publishing, 2021)
The article discusses in more detail the purpose and content of the EUMC structural components by the example of the manual on the discipline